A novel infrared freeze drying (IRFD) technology to lower the energy consumption and keep the quality of Cordyceps militaris. (June 2019) - Wu, Xiao-fei; Zhang, Min; Bhandari, Bhesh
Abstract: A novel laboratory scale apparatus using infrared lamps replacing the electric heating plate for the freeze drying of Cordyceps militaris was developed in this study. The drying time, energy consumption, nutritional properties, antioxidant activities and main volatile compounds of Cordyceps militaris dried by infrared freeze drying (IRFD) and traditional freeze drying (TFD) at different drying temperatures (40, 50, 60 and 70 °C) were compared. Results indicated that drying at 40, 50 and 60 °C resulted in higher retention of cordycepin, total phenolics, hydroxyl radical scavenging activity, reducing power, 3-octanone, 3-octanol and 1, 3-octadiene when compared with those dried at 70 °C. IRFD could reduce 7.21–17.78% of the drying time and 11.88–18.37% of the energy consumption at a constant drying temperature in comparison of TFD. In terms of quality, IRFD and TFD had similar retention effects on cordycepin, adenosine, hydroxyl radical scavenging activity and reducing power. Consequently, the results suggest that IRFD should be a promising approach for achieving high-quality dried products. Industrial relevance. IRFD could reduce 7.21–17.78% of the drying time and 11.88–18.37% of the energy consumption at a constant drying temperature in comparison of TFD without compromising the quality of the dried product. This study can help food processing industries to produce high quality freeze dried Cordyceps militaris and many other foods with an energy efficient freeze drying process. Highlights: A novel infrared freeze drying device (IRFD) was developed for the drying of Cordyceps militaris. Compared to TFD, IRFD could reduce 7.21–17.78% of the drying time at a constant drying temperature. IRFD could reduce 11.88–18.37% of the energy consumption compared to TFD at the same temperature. The quality of IRFD samples was close to that of TFD samples.